2021
DOI: 10.1093/sysbio/syab020
|View full text |Cite
|
Sign up to set email alerts
|

Inferring the Total-Evidence Timescale of Marattialean Fern Evolution in the Face of Model Sensitivity

Abstract: Phylogenetic divergence-time estimation has been revolutionized by two recent developments: 1) total-evidence dating (or ”tip-dating”) approaches that allow for the incorporation of fossils as tips in the analysis, with their phylogenetic and temporal relationships to the extant taxa inferred from the data, and 2) the fossilized birth-death (FBD) class of tree models that capture the processes that produce the tree (speciation, extinction, and fossilization), and thus provide a coherent and biologically interp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 146 publications
1
41
0
Order By: Relevance
“…All else being equal, dated analyses using a Fossilized Birth-Death model are expected to reconstruct fossil terminals as originating from deeper nodes than modern terminals, particularly when phylogenetic signal in the character data that might otherwise overwhelm the temporal signal is weak (Lee and Yates, 2018;King, 2020). In addition, most current implementations of Fossilized Birth-Death models, including in the dated total-evidence analysis presented here, assume constant rates of speciation, extinction, and fossilization/sampling through time and between lineages (although this is assumption can be relaxed; Stadler et al, 2013;Gavryushkina et al, 2014;Barido-Sottani et al, 2020;Magee and Höhna, 2021;May et al, 2021). This assumption means that long, unsampled branches will be disfavoured, such that fossil terminals are shifted to deeper positions if fossil sampling is not consistent throughout the tree (Turner et al, 2017;King, 2020).…”
Section: Dated Total-evidence Analysismentioning
confidence: 99%
“…All else being equal, dated analyses using a Fossilized Birth-Death model are expected to reconstruct fossil terminals as originating from deeper nodes than modern terminals, particularly when phylogenetic signal in the character data that might otherwise overwhelm the temporal signal is weak (Lee and Yates, 2018;King, 2020). In addition, most current implementations of Fossilized Birth-Death models, including in the dated total-evidence analysis presented here, assume constant rates of speciation, extinction, and fossilization/sampling through time and between lineages (although this is assumption can be relaxed; Stadler et al, 2013;Gavryushkina et al, 2014;Barido-Sottani et al, 2020;Magee and Höhna, 2021;May et al, 2021). This assumption means that long, unsampled branches will be disfavoured, such that fossil terminals are shifted to deeper positions if fossil sampling is not consistent throughout the tree (Turner et al, 2017;King, 2020).…”
Section: Dated Total-evidence Analysismentioning
confidence: 99%
“…In Bayesian phylogenetic inference, different model assumptions and their impact on tree topology or other parameters of interest can be tested. Most commonly, these model assessments are done using Bayes factors and stepping-stone analyses [ 13 ]. However, although studies have shown that the data selection (i.e., taxa and characters) can significantly impact analyses under the FBD model [ 14 , 15 ], objective criteria for selecting different sets of taxa or characters are rarely employed.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies advocated that MRC trees should generally be preferred because MCC trees may contain spurious clades that are poorly supported by the data [ 17 19 ]. However, low posterior probabilities are typical for many trees containing fossil data [ 13 , 20 , 21 ]. MRC trees therefore have the potential to provide limited information about tree topology, from a systematic perspective, if uncertainty is high.…”
Section: Introductionmentioning
confidence: 99%
“…These approaches are often referred to as tipdating or total-evidence dating. Although very attractive and promising in principle, they also require a number of assumptions, their behaviour is only starting to become better understood (Gavryushkina et al, 2017;May et al, 2021), and they have not yet been applied to angiosperms as a whole in the published literature.…”
Section: How To Estimate the Crown-group Age Of Angiospermsmentioning
confidence: 99%
“…As noted above, these methods are still in their infancy and their behaviour remains incompletely understood. For instance, May et al (2021) observed that the type of tree prior had a critical influence on estimated divergence times in tip-dating analyses of a group of ferns. Nevertheless, it is possible that, with time and sufficient exploration of these methods, adequately parameterized tip-dating approaches will ultimately help narrow down the range of plausible ages for crown angiosperms.…”
Section: Moving Forwardmentioning
confidence: 99%